PENGARUH DISIPLIN, KOMPETENSI DAN MOTIVASI GURU TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH PERTAMA NEGERI (SMPN) DI KECAMATAN GELUMBANG KABUPATEN MUARA ENIM - Faidol Azmi; Sakdiawati Sakdiawati; Mustopa Marlibatubara (STIE DWI SAKTI BATURAJA, 2019)
This study aims to determine the effect of discipline, competence and teacher motivation both jointly and partially on teacher performance in State Junior High Schools (SMP) in Gelumbang Subdistrict The design used in this study is correlational design. The population of this study were Gelumbang District Junior High School teachers, totaling 168 teachers. The sample of this study was calculated by the Slovin formula for a population of 168 teachers with an error rate of 10%, the total sample was 63 teachers as respondents. The first sample was tested using the Instrument Test (questionnaire) in the form of validity test and reliability test. The analysis model used in this study is multiple linear regression analysis. Regression calculations can be Y = 0.982 + 0.205X1 + 0.350X2 + 0.203X3. Interpretation of multiple regression equations regarding the effect of Work Discipline Variables (X1), Teacher Competence (X2), and Motivation (X3), on Bound Variables namely Teacher Performance (Y). The results of this calculation show that, the three independent variable coefficients are positive, this shows a positive linear relationship between the Variables of Work Discipline, Teacher Competence, and Motivation, on Teacher performance. The calculation of the correlation (R) is 0.799, the correlation coefficient means that the relationship between the two significant variables (free and bound) shows a strong level of closeness. The determination coefficient R2 = 0.638 means that the Work Discipline Variables (X1), Teacher Competence (X2), and Motivation (X3) are able to explain the Variable Teacher Performance (Y) of 0.638 or 63.8%, while the remaining 36.2% explained by other factors not examined. This study concludes that the discipline, competence and motivation of teachers both jointly and partially significantly affect teacher performance in State Junior High Schools in Gelumbang District.